Going Concern Opinions and the Market's Reaction to Bankruptcy Filings. - Chen, Kevin C. W.; Church, Bryan K. (The Accounting Review, 1996)
Abstract This study investigates the association between going concern opinions and the market's reaction to bankruptcy filings. The results of prior studies indicate that going concern opinions are useful in predicting bankruptcy and provide some explanatory power in predicting bankruptcy resolution. As such, going concern opinions may reduce the surprise associated with bankruptcy. Our results are consistent with this assertion. Firms receiving going concern opinions experience less negative excess returns in the period surrounding bankruptcy filings than those receiving unqualified opinions. These results hold after controlling for the probability of bankruptcy, the market's reaction to news announcements occurring prior to bankruptcy, and changes in stock price prior to the issuance of the auditor's report. Overall, our results are consistent with going concern opinions having information value.